Sum of Squared Difference (SSD) Template Matching Testing on Writing Learning Application - Sidi, Widya Dharma; Arta Wibawa, I Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 8 No 4 (2020): JELIKU Volume 8 No 4, Mei 2020DO - 10.24843/JLK.2020.v08.i04.p11, 2020)
Abstract This research was conducted to determine the accuracy of the Sum of Squared Difference (SSD) Template Matching method in the Application of Learning Numbers Writing Games. This game application is an application created to help early childhood in recognizing Arabic numbers, namely numbers from 0 to 9. In the SSD Template Matching method there are several processes including Preprocessing, thinning, feature extraction, and classification (SSD template matching). In testing the game application involves 10 respondents who were asked to write numbers correctly as requested by the application. For each number writing test, it is tested by 3 times. From the tests conducted, obtained an accuracy of 94.67%. Keyword: Template Matching, Sum of Squared Difference (SSD), Education Game, Optical Character Recognition, Mobile Learning